Regulation of biofilm formation in Pseudomonas and Burkholderia species - Fazli, Mustafa (2014)
In the present review, we describe and compare the molecular mechanisms that are involved in the regulation of biofilm formation by Pseudomonas putida, Pseudomonas fluorescens, Pseudomonas aeruginosa and Burkholderia cenocepacia. Our current knowledge suggests that biofilm formation is regulated by cyclic diguanosine-5′-monophosphate (c-di-GMP), small RNAs (sRNA) and quorum sensing (QS) in all these bacterial species. The systems that employ c-di-GMP as a second messenger regulate the production of exopolysaccharides and surface proteins which function as extracellular matrix components in the biofilms formed by the bacteria. The systems that make use of sRNAs appear to regulate the production of exopolysaccharide biofilm matrix material in all these species. In the pseudomonads, QS regulates the production of extracellular DNA, lectins and biosurfactants which all play a role in biofilm formation. In B. cenocepacia QS regulates the expression of a large surface protein, lectins and extracellular DNA that all function as biofilm matrix components. Although the three regulatory systems all regulate the production of factors used for biofilm formation, the molecular mechanisms involved in transducing the signals into expression of the biofilm matrix components differ between the species. Under the conditions tested, exopolysaccharides appears to be the most important biofilm matrix components for P. aeruginosa, whereas large surface proteins appear to be the most important biofilm matrix components for P. putida, P. fluorescens, and B. cenocepacia.